Adolescent borderline personality disorder: Does early intervention 'bend the curve'?. (December 2022) - Allison, Stephen; Bastiampillai, Tarun; Looi, Jeffrey CL; Mulder, Roger
Objective: The Global Alliance for Prevention and Early Intervention for Borderline Personality Disorder (BPD) proposed a major change for youth mental health services. The Alliance recommended that early detection and specialised treatment for youth BPD becomes a major focus of their clinical activities. Since structured psychotherapies for BPD are complex and lengthy, this proposal has significant implications for youth policy, planning and resource allocation. Our commentary addresses whether BPD is diagnosable and treatable in youth, and whether early intervention results in longer-term benefits. Conclusion: People diagnosed with BPD are highly heterogeneous and experience high levels of comorbidity. The low quality of the evidence for the treatment of BPD in adolescence limits our ability to develop evidence-based guidelines. Accordingly, there is no clear case for BPD early intervention as a major component of youth mental health services. The introduction of ICD-11 classification system may facilitate further empirical studies of personality disorders in adolescence and emerging adulthood.